Ambient Air Pollution Exposure and Adverse Outcomes Among Medicare Beneficiaries With Heart Failure - Amgad Mentias; Milind Y. Desai; Ambarish Pandey; Issam Motairek; Rohit Moudgil; Chonyang Albert; Salil V. Deo; Robert D. Brook; Venu Menon; Sanjay Rajagopalan; Sadeer Al‐Kindi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Exposure to fine particulate matter (<2.5 um, particulate matter with an aerodynamic diameter <2.5 microns [PM2.5]) has been implicated in atherogenesis. Limited data in animal studies suggest that PM2.5 exposure leads to myocardial fibrosis and increased incidence of heart failure (HF). Whether PM2.5 is associated with adverse outcomes in patients with preexisting HF has not been widely studied. Methods and Results In this retrospective cohort study, Medicare patients hospitalized with first HF between 2013 and 2020 were identified from the Medicare Provider Analysis and Review Part A 100% files. Patients were linked with integrated estimates of ambient PM2.5 obtained at 1×1 km using the zip code of participants' residence. The study outcomes were all‐cause death, HF, and all‐cause readmissions burden. A total of 2 599 525 patients were included in this study, with 6 321 731 person‐years of follow‐up. Mean PM2.5 was 7.3±1.7 μg/m3. Each interquartile range of PM2.5 was associated with 0.9% increased hazard of all‐cause death, 4.5% increased hazard of first HF readmission, 3.1% increased risk of HF hospitalization burden, and 5.2% increase in all‐cause readmission burden, after adjusting for 11 sociodemographic and medical factors. Subgroup analyses showed that the effects were more pronounced at levels <7 μg/m3 and in patients aged <75 years, Asians, and those residing in rural areas. Conclusions Ambient air pollution is associated with higher risk of adverse events in Medicare beneficiaries with established HF. These associations persist below the National Air Quality Standards (12 μg/m3), supporting that no threshold effect exists for health effects of air pollution exposure.